Peningkatan Ekonomi Kreatif dan Kewirausahaan Masyarakat Desa di Tengah Pandemi COVID 19 - Lanto Ningrayati Amali; Sitti Suhada; Muhammad Rifai Katili (Jurnal Sibermas (Sinergi Pemberdayaan Masyarakat), 2020)
The coronavirus pandemic or COVID 19 resulted in the disruption of almost all sectors of human life, ranging from the health, social, and economic life of the community. The goal that this activity wants to achieve is to increase the creativity and economy of the community in the mids of the spread of the COVID 19 outbreak. Special targets that want to be achieved are: (1) increasing the role of the community in creating entrepreneurship in the midst the COVID 19 outbreak, (2) improving people's ability to innovate by creating business ideas that suit the conditions amid during in the COVID 19 outbreak, and (3) the formation of a resilient society against the COVID 19 pandemic. To achieve these specific goals and targets the method used is by transferring science and technology based on information technology through the implementation of socialization, education, and training to the community as well as more accurate reports of public circumstances.